Evaluation on the utilization of modified agents for asphalt paving mixtures in Thailand highway construction - Chavalert Lertchavanakul; Yordphol Tanaboriboon; Prapansak Buranaprapa; Shimazaki, Toshikazu; Hokao, Kazunori; Royal Thai Government (Bangkok : Asian Institute of Technology, 1993)
It is recognized that polymer-modified agents or modifiers play a special role in asphalt cement or binder contained in asphalt concrete mixtures. Several examinations have found that the addition of these modifiers to asphalt cement improves the physical properties of the mix. Though many different types of modifiers are known, ARBOCEL and STYRELF are more prevalent because of the better performance of asphalt paving mixtures mixed with them and their simplicity to use for Thailand highway construction. The suitabilities of ARBOCEL and STYRELF as modified agents for asphalt concrete mixtures were examined in this research. Viscous Test, Elastic Test and Thermal of binders incorporating these modifiers were measured and compared to the properties of an original asphalt cement, AC 60170. Marshall mix design and Stability test were performed on Marshall specimens both without and with addition of these modifiers in various quantities for obtaining the optimum binder content of each quantity. Creep Compliance Test, Tensile Strength Test, Resilient Modulus Test, Fatigue Test, Moisture Damage Sensitivity Test and Weathering Treatment Test were performed on all Marshall specimens at optimum binder content. Physical properties of both original and modified asphalt mixtures were measured and compared each other. The results showed that adding ARBOCEL or STYRELF at certain percentages can produce a mixture of better properties than a mixture without an added modifier, namely, increase resistance to rutting and cracking, increase resistance to aging caused by fatigue and moisture. The results also showed that STYRELF is more potential than ARBOCEL in terms of improving the physical properties of asphalt concrete mixtures, however its life-cycle cost is higher than that of the ARBOCEL additive.
A thesis submitted in Partial Fulfillment of the Requirement for the Master Degree of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1993
Keywords: Asphalt cement